Análisis socio- jurídico sobre la inasistencia de las víctimas de violencia intrafamiliar” - Palomo Chisaguano, Lus Patricio (2015)
Domestic violence affects the full exercise of human rights, be they civil, economic, social or cultural; is a major problem with occurrence in the different strata of society; is inserted into households, shows a situation of discrimination in which women live, not only in our country but throughout the world by the mere fact of being women; even in developed countries women are subjected to violence. According to the World Report on Violence and Health, intimate partner violence exists in all societies, cultures and socioeconomic levels and includes physical, sexual and psychological abuse. The causes of this problem are different. A and foremost is economic, especially in those households where the household head brings more money than women, allowing the man to exercise power over women, this is also related machismo, direct influence the culture in which we live Ecuadorians. Viewed this way, violence becomes an obstacle to fully comply with work requirements. This situation alienates people, in some cases physically, psychologically or in other combinations with both situations, encourages absenteeism. Domestic violence affects productivity because women who suffer some type of violence are unable to go to work because of the aftermath left by the assault by their partners or ex-husband. This also represents a cost to health systems and services psychological treatment. It generates devaluation abuse, low self-esteem and emotional stress, resulting in poor work performance and concentration difficult, which may jeopardize their employment